The benefits of linking CGE and microsimulation models: evidence from a flat tax analysis - Andreas Peichl (Institute for the Study of Labor (IZA), 2008)
Mircrosimulation models (MSM) and Computable General Equilibrium models (CGE) have both been widely used in policy analysis. The combination of these two model types allows the utilisation of the advantages of both types. The aim of this paper is to describe the state-of-the-art in simulation and to demonstrate the benefits of linking both model types modelling flat tax reform proposals for Germany. Taking the general equilibrium effects into account has important implications for the evaluation of a tax reform. The analysis shows that a personal income flat tax can indeed overcome the fundamental equity efficiency trade-off in the long-run while simultaneously increasing the tax revenue. However, this result does not hold for a flat tax combining a personal income flat tax with a corporate cash flow flat tax, even when allowing for an ex-post loss in revenue.
urn:nbn:de:101:1-20081014142
Keywords: D58; 330; Microsimulation; CGE; linked micro macro models; flat tax; Mikrosimulation; Allgemeines Gleichgewicht; Flat Tax; Einkommensteuer; Steuerreform; Steuerwirkung; Simulation; Theorie; Deutschland